Simultaneous Unbinned Differential Cross-Section Measurement of Twenty-Four Z+jets Kinematic Observables with the ATLAS Detector - Aad, G; Aakvaag, E; Abbott, B; Abdelhameed, S; Abeling, K; Abicht, N J; Abidi, S H; Aboelela, M; Aboulhorma, A; Abramowicz, H; Abreu, H; Abulaiti, Y; et al. (Physical review letters, 2024)
Z boson events at the Large Hadron Collider can be selected with high purity and are sensitive to a diverse range of QCD phenomena. As a result, these events are often used to probe the nature of the strong force, improve Monte Carlo event generators, and search for deviations from standard model predictions. All previous measurements of Z boson production characterize the event properties using a small number of observables and present the results as differential cross sections in predetermined bins. In this analysis, a machine learning method called omnifold is used to produce a simultaneous measurement of twenty-four Z+jets observables using 139 fb^{-1} of proton-proton collisions at sqrt[s]=13 TeV collected with the ATLAS detector. Unlike any previous fiducial differential cross-section measurement, this result is presented unbinned as a dataset of particle-level events, allowing for flexible reuse in a variety of contexts and for new observables to be constructed from the twenty-four measured observables.